(3cJGH aj Gdhbas - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B.. (3cJGH Gdhba hGdUObGJ (B, (3Gdhba dZI GdMHS hGdJMHjS jJYOi hdG jJYOi jbGd hba Ydjg hhbaJg hgh eTJQc HjfgeG daXG EP dG LGeY HjfgeG hJMejd Gf jchf MbjbI aj GdeJYOj (B...s
(3BNQgG (B:s
.. (3eSJbd eVehf Ydi GdbGHV hEf cGf dG hLhO dgG NGQLG (B.. (3Vef GdYjf GdQGHY Cf JDRQ GdCUhd aj Mce Gdhba aj dRhe GdbjeI Ydi GdZGUH ceG dh SQb GdeGd Ch ZUH Ch aQb Gh ZjQ Pdc (B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis